Special Collection on Community-Led Strategies to Reduce Gun Violence: Developing Evidence for Policy and Practice: An Editorial. - Butts, Jeffrey A.; Roman, Caterina G. (Inquiry (00469580), 2026)
The article focuses on the development and evaluation of community violence intervention (CVI) programs in the United States, which aim to reduce violence through community-led efforts rather than solely relying on law enforcement. It highlights the diversity of CVI models, emphasizing the importance of community resources, relationship-building, and public health frameworks in addressing the root causes of violence. Despite increased federal funding for CVI initiatives post-2020, recent political changes have led to significant funding cuts, hindering research and evidence collection on the effectiveness of these programs. The article calls for a stronger evidence base to support community-led CVI approaches, advocating for rigorous evaluations that can demonstrate their impact on violence reduction.